Built environment associates of active school travel in New Zealand children and youth: A systematic meta-analysis using individual participant data. (June 2018) - Ikeda, Erika; Stewart, Tom; Garrett, Nicholas; Egli, Victoria; Mandic, Sandra; Hosking, Jamie; Witten, Karen; Hawley, Greer; Tautolo, El Shadan; Rodda, Judy; Moore, Antoni; Smith, Melody
Abstract: This systematic review and meta-analysis examined the associations between active travel to school and the neighbourhood built environment in children and youth by systematically identifying and collating data from New Zealand studies. Data from five studies involving 2844 children and youth aged 6–19 years were included in the meta-analysis. Data on participant demographics and school characteristics were obtained from each study, and built environment features within 400 m and 1 km buffers around home were calculated in a consistent manner using geographic information systems. A one-step individual participant data meta-analysis was performed in SAS. Using stepwise logistic regression, age, school socioeconomic status, distance to school, dwelling density and intersection density (400 m and 1 km buffers) were taken forward from bivariate analyses into a multiple variable model. Active travel to school was positively associated with intersection density (p < 0.001) (1 km buffer) and negatively associated with school socioeconomic status (p = 0.001), dwelling density (p = 0.004) (1 km buffer), and distance to school (p < 0.001), including age, sex, ethnicity and number of siblings as fixed effects in the final model. The findings of this meta-analysis can be used to guide and support the development of policies on school location and catchment, and pedestrian and cycling infrastructure for children and youth to actively and safely travel to school. Graphical abstract: fx1 Highlights: Distance to school was the strongest predictor of active travel to school. Increased street connectivity around schools was related to active travel to school. Dwelling density was negatively associated with active travel to school. School socioeconomic status was negatively associated with school travel mode. Distance to school is a key consideration for school zoning and catchment policies.